A Randomized, Double-Masked, Active-Controlled, Crossover Phase III Equivalence Study of Generic Dorzolamide 2% versus Innovator Trusopt® Eye Drop Solution in Subjects with Open-Angle Glaucoma or Ocular Hypertension. (20th July 2022) - Bell, Katharina; Korb, Christina; Butsch, Christina; Giers, Bert Constantin; Beck, Anna; Strzalkowska, Alicja; Ruckes, Christian; Klingberg, Ulrike; Pfeiffer, Norbert; Lorenz, Katrin
Abstract : Background . The aim of this study was to demonstrate the equivalence of generic dorzolamide 2% eye drops solution versus the innovator formulation (Trusopt® eye drops solution) in patients with open-angle glaucoma or ocular hypertension. Methods . This prospective, monocentric, double-masked, active-controlled crossover phase III study included 32 patients. After washout, patients were randomized to reference product (Trusopt®) or test product (dorzolamide 2% eye drops, Rompharm Company SRL) for a 4-week period. Subsequent washout and crossover were performed. Drops were applied t.i.d. The primary efficacy endpoint was the difference in mean diurnal IOP. Goldmann applanation tonometry was performed at 8 am, 12 pm, and 4 pm at each visit, and safety was assessed by documentation of adverse events (AEs). Therapy adherence was documented by self-reporting and eye drop bottle weighing. An ANOVA with treatment, sequence, study period, and patient within the sequence as effects was performed and an additional post hoc ANCOVA including the baseline IOP was also performed. Results . 34 patients were randomized and analyzed in the safety population. The per-protocol population included 32 patients. According to the self-report, all patients were >80% compliant. Under the ANCOVA model, the 90% confidence interval for the average change of the IOP −0.27 mmHg (−1.17 mmHg–0.64 mmHg) is included by the acceptance range −1.5 mmHg to +1.5 mmHg after excluding 2 patients, which had falsely reported high therapy adherence. No clinically relevant difference was observed in frequency or severity of the AEs between both treatments. Conclusions . This study showed the equivalence of the tested generic dorzolamide 2% eye drops solution to the reference product Trusopt® eye drops solution. Trial Registration. This trial is registered with (ClinicalTrials.gov (identifier: NCT00878917 ) on April 9, 2009).